A Critical Review on the Book An Approach to Realism, Cinema and the Expression of Religious Concepts - Ali Khorashadi; Dariush Esmaeili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Realism is a powerful materialization of art that appeared in 19th century in literature and painting and is still ongoing. A realism artist creates logic and relations in a work of art that comes from new sciences and social relations related to modern society. Meanwhile, Cinema as modern era art has close connections with realism for image recording and we know that from the earliest films of Lumiere brothers. with the addition of sound and color to basic silent movies, this relation continued and from mid 20th-century attitudes for social realism were increased which was reflected in works of Iitalian Neorealists and “Andre Bazin” theories. This article is a survey of the book An Approach to Realism, Cinema and the Expression of Religious Concepts that was written by Vahid Hayati that surveyed the capacities of cinema realism to express religious concepts and it is about distinguishing the common realism that reaches its climax at Neorealism movement, and a form of realism that is common to express religious concepts. In this article, Hayati’s opinions about the religious realism concept were shown. He believes this manifested in the works of Majid Majidi and especially “Children of Heaven”. It criticized his point of view about similarities between realism in Islamic and religious concepts and cinematic concept and differences based on epistemology.